Memahami Teori Pembelajaran Kognitif dan Konstruktivisme serta Penerapannya - Habsy, Bakhrudin All; Christian, Jerry Sheva; M, Syifa’ul Ummah Salsabila Putri; Unaisah, Unaisah (TSAQOFAH, 2024)
Cognitive theories of learning have had a significant impact on modern education. It focuses on individual cognitive development, emphasizing creativity, deep understanding and meaningful learning. In its implementation, several learning models such as constructivism, discovery learning and meaningful learning become relevant. The advantages of cognitive theory include encouraging students' creativity, developing individualized knowledge, flexibility in learning, and improving memory. However, there are also drawbacks, such as lack of comprehensiveness at all levels of education and limitations in addressing individual student differences. This article summarizes the main concepts of cognitive theory in learning, and identifies the advantages and disadvantages associated with its implementation. A better understanding of this theory can help educators create a more effective learning environment that suits the diverse needs of students.